Oral History Program Interview: Charles M. Newsome - Newsome, Charles M.
Newsome's interview includes perspectives on racial issues, prejudice toward "Okies," family life on the farm before and after settling in California, and cotton camp life for themselves and, later, their own workers. Born on December 24, 1926 outside Fort Gibson, Oklahoma, Newsome and his family traveled to Woodville, California in October of 1935. His racial perspectives provide insight on the societal views towards African Americans and Mexicans. He clearly describes the complex nature of the term "Okie" as derogatory, not in a racial or ethnic way, but as an economic class.